Recent developments in boundary element methods : a volume to honour Professor John T. Katsikadelis - Katsikadelis, John T.; Sapountzakis, E. J. (Evangelous J.) (Southampton, U. K. : WIT, 2010)
A collection of contributions on the latest developments in the fields of boundary element methods and other mesh reduction methods, this text honours the work of John T. Katsikadelis.
Includes bibliographical references and index.
Keywords: Boundary element methods